High-temperature time domain measurement system for solid and molten materials. (4th September 2018) - Orr, G; Ben Ishai, P; Roth, M
Abstract: A low-cost time domain system for measuring dielectric relaxation in the frequency range of 1 Hz–1 MHz of solid and molten materials at high temperatures is described in detail. A parallel plate electrode sample cell is described that can hold molten material by capillary action. In order to avoid electrical breakdown or a change in electrode distance due to opposite charge buildup, the step voltage can be set to the mV range. At this level interference noise affects the measurements and active filtering is required. The resulting signal is captured using a digital storage oscilloscope. An algorithm for reducing the measured data prior to data processing is discussed. The system is calibration free and its upper temperature is limited only by the construction materials of the furnace and electrodes. Molten NaCl is presented as a test sample.